Genetic divergence in sweet cassava cultivars using morphological agronomic traits and RAPD molecular markers - Fabrício Rimoldi; Pedro Soares Vidigal Filho; Marcus Vinícius Kvitschal; Maria Celeste Gonçalves-Vidigal; Alberto José Prioli; Sônia Maria Alves Pinto Prioli; Tiago Ribeiro da Costa (Brazilian Archives of Biology and Technology, 2010)
In this work the genetic divergence among 14 sweet cassava cultivars was estimated by their morphological agronomic traits and RAPD molecular markers. The Tocher cluster analysis and the Nearest Neighbor Method were applied. The most dissimilar cultivars were Pão and Guaíra, Fécula Branca and Pão, and Pão and Caipira, while the most similar cultivar were the Fécula Branca and Branca 1, Branca 3 and Branca 1, and Guaíra and Branca 1. The Jaccard's coefficient showed that the most similar cultivars were Guaíra and Quarenta Quilos, while the most dissimilar were Branca 3 and Amarela da Rama Cinza. The divergence analysis indicated that promising crosses could be made between the Branca 3 cultivar and the Pão, Amarela 1, Fécula Branca and Amarela 2 cultivars for the high genetic divergence, favorable agronomic and culinary traits, and disease resistance on the part of at least one of the parents involved in the cross. A divergência genética entre 14 cultivares de mandioca-de-mesa foi estimada mediante o uso de caracteres morfoagronômicos e de marcadores moleculares RAPD. As análises de agrupamento de Tocher e do Vizinho Mais Próximo foram efetuadas. As cultivares mais divergentes foram Pão e Guaíra, Fécula Branca e Pão, e Pão e Caipira, enquanto as mais similares foram Fécula Branca e Branca 1, Branca 3 e Branca 1, e Guaíra e Branca 1. O coeficiente de Jaccard indicou que as cultivares mais similares foram Guaíra e Quarenta Quilos, enquanto as mais dissimilares foram Branca 3 e Amarela da Rama Cinza. A análise de divergência indicou que cruzamentos promissores deveriam ser efetuados entre as cultivares Branca 3, Pão, Amarela 1, Fécula Branca e Amarela 2 pela alta divergência genética, características agronômicas e culinárias favoráveis, e resistência à doenças de parte de pelo menos um dos parentais envolvidos no cruzamento.